Pengaruh Online Learning dan Fraud Diamond Terhadap Prilaku Fraud Academic Dimasa Pandemi Covid 19 (Studi Kasus Mahasiswa Akuntansi Universitas Ekasakti Padang Angkatan 2019-2020) - Hakim, Arif Rahman; Rina Asmeri; Meriyani, Meriyani (Ekasakti Pareso Jurnal Akuntansi, 2024)
The purpose of this research is to find out how online learning and Fraud Diamond affect academic fraud during the Covid 19 Pandemic. This research focuses on accounting students class 2019–2020 at Unes Padang. In this study, fraud diamond has 4 sections reviewed, namely Pressure, Opportunity, Capability and Rationalization. 66 students is the number of samples used in this study. A survey method was used to collect data, and questions were distributed via Google forms. Multiple linear regression analysis is the data analysis method used, and the application program used is SPSS 25. Online learning, pressure, opportunity, ability, and rationalization are the factors used in this study. Academic deception is the dependent variable. The findings reveal that while the variables Opportunity, Ability, and Rationalization do not have a significant impact on academic cheating, the variables Online Learning and Pressure do. The results of the F test (simultaneous) revealed that learning courage, pressure, opportunity, capability, and rationalization together had a major impact on academic fraud among Unes Padang Accounting Students Class of 2019–2020.